2019
DOI: 10.18805/lr-4137
|View full text |Cite
|
Sign up to set email alerts
|

Devising selection criteria based on variability and association studies in segregating populations derived from an interspecific cross between Cajanus scarabaeoides × C. cajan

Abstract: Segregating populations (BC 1 F 3 and F 3:4 ) from an interspecific cross (C. scarabaeoides × C. cajan) were evaluated for variability and association studies for yield and its component traits. In both the generations, high values of PCV and GCV were obtained for pods per plant, seed yield per plant and fruiting branches per plant. High estimates of heritability as well as genetic advance were observed for fruiting branches per plant followed by pods per plant and seed yield per plant. High heritability coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…The association of pods per plant, secondary branches per plant, plant height and 100-seed weight with seed yield per plant was positive due to positive direct effects. Similar outcomes were also reported by Kothimbire et al (2016), Ram et al (2016), Kumar et al (2017), Ranjani et al (2018) and Singh et al (2019). Above results indicated that indirect selection for higher seed yield can be achieved through secondary branches per plant.…”
Section: Correlation and Path Coefficient Analysissupporting
confidence: 89%
See 3 more Smart Citations
“…The association of pods per plant, secondary branches per plant, plant height and 100-seed weight with seed yield per plant was positive due to positive direct effects. Similar outcomes were also reported by Kothimbire et al (2016), Ram et al (2016), Kumar et al (2017), Ranjani et al (2018) and Singh et al (2019). Above results indicated that indirect selection for higher seed yield can be achieved through secondary branches per plant.…”
Section: Correlation and Path Coefficient Analysissupporting
confidence: 89%
“…correlation with seed yield per plant. Pandey et al (2016), Pushpavalli et al (2017), Baldaniya et al (2018) and Singh et al (2019) also reported significant and positive correlation between seed yield per plant and number of pods per plant.…”
Section: Correlation and Path Coefficient Analysismentioning
confidence: 86%
See 2 more Smart Citations
“…The C. scarabaeoides (L.) Thouars, a wild relative of pigeonpea has agronomically superior characteristics, including dwarfness, the number of fruiting branches and pods per plant, and resistance to pod borers and phytophthora stem blight (Upadhyaya et al, 2013;Singh et al, 2020a). The yield-attributing genes from C. scarabaeoides have been successfully introgressed into the Pigeonpea (Singh et al, 2018a;Sharma et al, 2019;Singh et al 2020a;Singh et al 2021a). The wild accession of pigeonpea also served as the important source of male sterility genes.…”
Section: Pigeonpeamentioning
confidence: 99%